(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To synthesize current evidence on the efficacy and safety of biologic therapies in severe asthma and to provide practice-oriented guidance for treatment selection based on phenotype and biomarkers. Methods: This narrative review searched PubMed, Embase, the Cochrane Library, and Google Scholar up to October 31, 2025, using keywords related to severe asthma, difficult-to-treat asthma, and biologic agents. Eligible publications included practice guidelines, systematic reviews, umbrella reviews, and pivotal phase III clinical trials in patients aged 12 years and older. Results: Biologic agents, including omalizumab, mepolizumab, benralizumab, dupilumab, and tezepelumab, consistently reduced exacerbations, improved lung function, lowered oral corticosteroid requirements, and enhanced quality of life in appropriately selected patients. Omalizumab showed particular value in severe allergic asthma; mepolizumab and benralizumab were effective in eosinophilic asthma; dupilumab was suitable for patients with high type 2 inflammation and allergic comorbidities; and tezepelumab expanded treatment options for less typical phenotypes. Conclusion: Biologic therapy has fundamentally changed the management of severe asthma, but optimal benefit depends on selecting the right agent according to phenotype, biomarkers, treatment goals, comorbidities, and affordability.